PENGARUH GURU AL-QUR’AN HADITS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS MELALUI APLIKASI QUIZIZZ DI SEKOLAH MENENGAH KEJURUAN AL-IRSYAD AL-ISLAMIYYAH KOTA JAMBI - Andini Puspita Sari; Sukarno; Samsu (STKIP Subang, 2026)
This study discusses the use of Quizizz to improve student learning outcomes in the subject of Al-Qur’an Hadith at Sekolah Menengah Kejuruan (Vocational High School) Al-Irsyad Al-Islamiyyah Kota Jambi. This research is a quantitative study using the True Experimental-Pretest-Posttest Control Group Design method, while data collection was carried out through the Quizizz application. The results showed that the use of the Quizizz application had a significant effect on student learning outcomes in the Al-Qur’an Hadith subject. This is evidenced by the calculation result of the sig (2-tailed) value of P: 0.000 < 0.05, so it can be concluded that there is a significant difference. Thus, H0 is rejected and Ha is accepted. Based on these findings, this study suggests that teachers apply learning using the Quizizz application in the teaching of Al-Qur’an Hadith. Keywords: Quizizz, Student Learning Outcomes, Al-Qur’an Hadith